Testing enforcement strategies in the field: legal threat, moral appeal and social information - Gerlinde Fellner; Rupert Sausgruber; Christian Traxler (Max Planck Institute for Research on Collective Goods, 2009)
We run a large-scale natural field experiment to evaluate alternative strategies to enforce compliance with the law. The experiment varies the text of mailings sent to potential evaders of TV license fees. We find a strong alert effect of mailings, leading to a substantial increase in compliance. Among different mailing conditions a legal threat that stresses a high detection risk has a significant and highly robust deterrent effect. Neither appealing to morals nor imparting information about others' behavior enhances compliance. However, the information condition has a positive effect in municipalities where evasion is believed to be common. Overall, the economic model of crime performs remarkably well in explaining our data.
Keywords: K42; C93; 330; Field experiments; law enforcement; compliance; deterrence; Rechtsdurchsetzung; Normbefolgung; Feldforschung; Rundfunkfinanzierung; Schuldrecht; Deutschland